(untitled) (TUTA Journal, 2024)
This paper has studied how an author can resurrect and reconstruct the mythology of the Ramayana and how to bring necessary creative additions to the ancient story so that the resultant will be a new story. Katuwal’s novel Sitanjali is entirely based on the event of the Ramayana story. However, author’s creativity is diluted in such a way that the novel stands a complete masterpiece of a newly version of a Nepali novel. The methodology applied in the research is Gerard Genette’s structuralism. Katuwal’s Sitanjali is in a novel version of the Ramayana into a genre of Nepali novel written in a wide range of spectrum, which deems progressive and even subversive. This study is significant in order to disclose how the sidelined voices are given preference in these stories. There is an attempt to give the women characters their due status and that is why some of the novel’s event sequences make it a point to be viewed from the feminine perspective.